2012
DOI: 10.5018/economics-ejournal.ja.2012-33
|View full text |Cite
|
Sign up to set email alerts
|

Through Which Channels Can Remittances Spur Economic Growth in MENA Countries?

Abstract: This paper studies the remittances' effect on economic growth. Using panel data techniques, the authors estimate several specifications to provide support of such relationship for MENA countries over the period 1980-2009. The findings provide new robust evidence on how remittances are used in MENA countries and detect the main channels which may interfere in this process. Estimation outcomes show that the most important part of remittances is consumed and that remittances stimulate growth only when they are in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…A study exploring economic data of 62 developing countries from the period of 1990 to 2014 indicates that when the countries are more open, the remittance boosts the growth. Beside this, this study also claims that the cause behind this happening is that remittance is in itself not adequate for growth, the benefits of the remittance are depended on the macroeconomic environment and the quality of the domestic institution of the remittance receiving country (Dastidar, 2017).The investigation in MENA countries with data from 1980 to 2009 claimed influences of remittance indicates that the remittance stimulates the economic growth when the remittance is invested and it also contributes to growth by boosting the accumulation of human capital (Mim & Ali, 2012). A study of 8 labor-exporting MENA countries claimed influence of remittance is positive with investment and negative with saving at domestic level (Sabra, 2016).…”
Section: Literature Reviewmentioning
confidence: 91%
“…A study exploring economic data of 62 developing countries from the period of 1990 to 2014 indicates that when the countries are more open, the remittance boosts the growth. Beside this, this study also claims that the cause behind this happening is that remittance is in itself not adequate for growth, the benefits of the remittance are depended on the macroeconomic environment and the quality of the domestic institution of the remittance receiving country (Dastidar, 2017).The investigation in MENA countries with data from 1980 to 2009 claimed influences of remittance indicates that the remittance stimulates the economic growth when the remittance is invested and it also contributes to growth by boosting the accumulation of human capital (Mim & Ali, 2012). A study of 8 labor-exporting MENA countries claimed influence of remittance is positive with investment and negative with saving at domestic level (Sabra, 2016).…”
Section: Literature Reviewmentioning
confidence: 91%
“…Empirical evidence suggests that remittances can contribute positively to economic growth in the destination countries by alleviating food insecurity and increasing savings and investment [14]. More specifically, a study focused on Middle East and North Africa countries found that remittances are used for investments such as human capital, housing, and land rather than household consumption, and that there is a positive relationship between economic growth and remittances [15]. Additionally, in South Asia, economic growth from remittances has been achieved through education and financial sector development [16].…”
Section: Overview Of Remittances With a Focus On Healthmentioning
confidence: 99%
“…We measure trade openness (OPEN) by the sum of exports and imports to GDP. Trade openness is expected to exert a positive effect on growth given that openness facilitates the exchange of goods and improves capital allocation efficiency (Ben Mim and Ben Ali, ). We use government spending (GS) to control for the effect of fiscal policy on economic growth.…”
Section: Datamentioning
confidence: 99%
“…Openness is expected to be positively correlated to growth. By facilitating the exchange of goods and services and by improving capital allocation efficiency, openness can foster economic growth (Ben Mim and Ben Ali, ). Regarding the credit indicator (CPS), the correlation matrix suggests a positive correlation to GDP but a negative correlation to the GDP growth rate.…”
Section: Datamentioning
confidence: 99%